The Median Quartiles Test Revisited - von Eye, Alexander; Neubauer, Aljoscha; Stemmler, Mark (Studia Psychologica, 1996)
Describes R. K. Bauer's (1962) Median Quartiles Test, a strategy for simultaneously testing for homeopoetic and heteropoetic treatment effects in a 2-group experimental design. The strategy is based on H. O. Lancaster's (1949) chi-square partition of a 4 * 2 table with a dependent variable that has 4 ordinal categories. The test is reformulated to be suitable for assessing differences in location and orthogonal decomposition is introduced for detecting differences in locations and dispersion. One specific characteristic of the reformulated Bauer median quartiles test is that it does not need alignments in location for efficient detection of differences in location. Examples from drug research illustrate the use of the reformulated test.
Keywords: Nonparametric Statistical Tests; Treatment